Lipopolysaccharide infusion up-regulates hepcidin mRNA expression in equine liver - Oliveira-Filho, Jose P. [UNESP]; Badial, Peres R. [UNESP]; Cunha, Paulo H. J. [UNESP]; Peiro, Juliana R. [UNESP]; Araujo, Joao P. [UNESP]; Divers, Thomas J. [UNESP]; Winand, Nena J. [UNESP]; Borges, Alexandre Secorun [UNESP] (Sage Publications Ltd, 2012)
Hepcidin has been found to be the key regulator of iron metabolism that leads to hypoferremia during inflammation. Recent work has shown that equine hepcidin is predominantly expressed in the liver of horses. In this study, hepcidin gene expression was determined in the liver and bone marrow of six healthy horses after iv infusion of Escherichia coli O55:B5 LPS. The IL-6 gene expression was also determined in liver and bone marrow samples. Clinical and laboratory evaluations were measured at multiple time points between 0 and 240 h post-LPS infusion (PI). Liver and bone marrow biopsies were taken immediately before (baseline) and at 6 and 18 h PI. In response to endotoxin infusion, all horses showed characteristic clinical signs of endotoxemia. Plasma iron concentration was decreased significantly from the pre-infusion level at 8 h PI. Hypoferremia peak was observed at 12 h and returned to normal levels at 30 h PI. Relative real-time RT-PCR analysis showed that liver hepcidin and IL-6 mRNA expression was up-regulated at 6 h PI. Bone marrow hepcidin relative expression was not influenced by LPS infusion. In another experiment, equine monocyte cultures were stimulated with LPS (1 mu g/ml). Monocyte hepcidin and IL-6 gene expression was significantly induced after 2 h of LPS stimulus and returned to baseline levels thereafter. The present study describes that, in horses, LPS infusion up-regulates hepatic hepcidin mRNA expression resulting in early observed hypoferremia and suggests that hepcidin may act as an acute-phase protein in horses.
Keywords: Acute-phase reactants; endotoxins; hepcidin; inflammation; iron metabolism